2018
DOI: 10.17085/apm.2018.13.3.271
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oxycodone and fentanyl for postoperative patient-controlled analgesia after orthopedic surgery

Abstract: Background: Oxycodone is widely used as bolus or patient-controlled analgesia (PCA) for control of postoperative pain. The aim of this study was to assess the efficacy and side effects of oxycodone for somatic pain by comparing oxycodone and fentanyl intravenous PCA after orthopedic surgery.Methods: Seventy-three patients undergoing orthopedic surgery were randomly assigned to receive fentanyl or oxycodone using intravenous PCA (potency ratio 1:60). Pain severity at rest and with movement and adverse effects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…Oxycodone for somatic pain such as pain after orthopedic surgery, the amount of oxycodone should be higher than the dose used for visceral pain. In a study of seventy-three patients undergoing orthopedic surgery randomly assigned to receive fentanyl or oxycodone using intravenous PCA, they concluded that with a 1:60 ratio of oxycodone to fentanyl in the application of PCA for pain control, the use of larger doses of oxycodone for 6 hours is effective in controlling early postoperative pain [72].…”
Section: Oxycodonementioning
confidence: 99%

Postoperative Pain in Orthopedics

Trinidad Castillo García,
Estela Elizabeth Ortega Ponce,
Carolina Martínez Esparza
2023
Topics in Postoperative Pain
“…Oxycodone for somatic pain such as pain after orthopedic surgery, the amount of oxycodone should be higher than the dose used for visceral pain. In a study of seventy-three patients undergoing orthopedic surgery randomly assigned to receive fentanyl or oxycodone using intravenous PCA, they concluded that with a 1:60 ratio of oxycodone to fentanyl in the application of PCA for pain control, the use of larger doses of oxycodone for 6 hours is effective in controlling early postoperative pain [72].…”
Section: Oxycodonementioning
confidence: 99%

Postoperative Pain in Orthopedics

Trinidad Castillo García,
Estela Elizabeth Ortega Ponce,
Carolina Martínez Esparza
2023
Topics in Postoperative Pain
“…Sedangkan, pasien dengan komorbid pada kelompok fentanil kontinu 19 orang, lebih tinggi dibandingkan dengan kelompok ketorolak intravena sebesar 5 orang. Namun demikian, penelitian ini berbeda dengan penelitian lain yang pemilihan jenis analgetik yang diberikan kepada pasien tidak bergantung pada komorbid atau penyakit lain yang dialami pasien 52,53,54 .…”
Section: Pendahuluanunclassified